Left Ringing: Betelgeuse Illuminates the Connection between Convective Outbursts, Mode Switching, and Mass Ejection in Red Supergiants - Morgan MacLeod; Andrea Antoni; Caroline D. Huang; Andrea Dupree; Abraham Loeb (The Astrophysical Journal, 2023)
Betelgeuse, the nearest red supergiant, dimmed to an unprecedented level in early 2020. The star emerged from this “Great Dimming” episode with its typical, roughly 400 days pulsation cycle halved, and a new dominant period of around 200 days. The dimming event has been attributed to a surface mass ejection, in which rising material drove shocks through the stellar atmosphere and expelled some material, partially obscuring the star as it formed molecules and dust. In this paper, we use hydrodynamic simulations to reveal the connections between Betelgeuse's vigorously convective envelope, the surface mass ejection, and the pulsation mode switching that ensued. An anomalously hot convective plume, generated rarely but naturally in the star's turbulent envelope, can rise and break free from the surface, powering an upwelling that becomes the surface mass ejection. The rising plume also breaks the phase coherence of the star's pulsation, causing the surface to keep expanding even as the deeper layers contract. This drives a switch from the 400 days fundamental mode of pulsation, in which the whole star expands and contracts synchronously, to the 200 days first overtone, where a radial node separates the interior and exterior of the envelope moving in opposite phase. We predict that the star's convective motions will damp the overtone oscillation and Betelgeuse will return to its previous, 400 days fundamental-mode pulsation in the next 5–10 yr. With its resolved surface and unprecedentedly detailed characterization, Betelgeuse opens a window to episodic surface mass ejection in the late-stage evolution of massive stars.